Optimisation of Retsina Wine Quality: Effects of Resin Concentration, Yeast Strain, and Oak Chip Type - Pantelis I. Natskoulis; Dimitrios-Evangelos Miliordos; Apostolos N. Koutsouris; Petros A. Tarantilis; Christos S. Pappas; Stamatina Kallithraka; Yorgos Kotseridis; Maria Metafa (Foods)
Retsina, Greece’s most renowned traditional wine, has been produced for millennia, with archaeological and historical evidence supporting its legacy. It is legally defined as wine made exclusively in Greece using grape must infused with Aleppo pine resin (Pinus halepensis). This study examines the effects of varying resin concentrations (0.5 g/L and 1 g/L), two commercial yeast strains, and medium-toast oak (Nadalié Cooperage, Ludon-Médoc, France) American and French, on Retsina’s chemical and sensory properties to optimise its production. Wine samples from the Savatiano grape variety were analysed for classical wine parameters, oxidation stability, volatile compounds, organic acids, phenolic profiles, and sensory attributes. Principal Component Analysis (PCA) revealed that yeast strain selection significantly influences chemical composition, with Zymaflore X5 associated with higher organic acid levels. Oak addition altered phenolic profiles, with American oak increasing ellagic acid, while non-oaked wines showed higher syringic and p-coumaric acids. Resin addition elevated alpha-pinene, a key marker of resin aroma, but reduced esters linked to fruity and floral notes. These findings highlight the complex interactions between resin, yeast, and oak, offering insights for enhancing Retsina’s quality while preserving its traditional character.